Wisata Gua Pawon Menjadi Wisata Edukasi untuk Bidang Geografi - Muhammad Ghani Kurnia; Shannaz Kayla Martza (Inovasi Pendidikan dan Anak Usia Dini, 2024)
The aim of this research is to analyze the potential of Pawon Cave as education in the field of geography. The method used in this research is a qualitative method through data collection. The results of this research are to identify the Pawon Cave Area through geography, demographics, social, economic, cultural and environmental. The potential that exists in Pawon Cave to become an educational tourist attraction in the field of geography is that a master plan for the area is planned to include Pawon Cave tourism which is ready to support the area into educational tourism in the field of geography as well as collaborating with other parties such as academics, government institutions, communities and the public local.